2007
DOI: 10.1254/jphs.fmj06003x6
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms in the CNS and Peripheral Clock Disorders: Chronopharmacological Findings on Antitumor Drugs

Abstract: Abstract. The effectiveness and toxicity of antitumor drugs vary depending on dosing time associated with the 24-h rhythms of biochemical, physiological, and behavioral processes under the control of the circadian clock. Such chronopharmacological phenomena are influenced by not only the pharmacokinetics but also pharmacodynamics of medications. For example, the antitumor effect and / or toxicity of irinotecan hydrochloride, interferon, and antiangiogenic agents vary depending on the dosing time associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The master mammalian biological clock is located in the hypothalamic suprachiasmatic nuclei (SCN) which imposes its temporal structure on the organism via neural and endocrine outputs [1,2]. The SCN harbors the master circadian clock that coordinates most aspects of behavior and physiology [3,4]. This endogenous clock is responsible for biological rhythms which are influenced by synchronizing factors such as light, temperature and food intake [5].…”
Section: Introductionmentioning
confidence: 99%
“…The master mammalian biological clock is located in the hypothalamic suprachiasmatic nuclei (SCN) which imposes its temporal structure on the organism via neural and endocrine outputs [1,2]. The SCN harbors the master circadian clock that coordinates most aspects of behavior and physiology [3,4]. This endogenous clock is responsible for biological rhythms which are influenced by synchronizing factors such as light, temperature and food intake [5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous animal experiment studies have demonstrated that the toxicity of drugs is significantly changed when administrated at various time points. Clinical evidences has also proven that optimal dosing‐time in a 24‐hour period can augment the therapeutic efficacy, increase overall survival rates and reduce toxicity in cancer patients [16–17]. Usually, toxicity in the daylight is less than in darkness for humankind.…”
Section: Discussionmentioning
confidence: 99%
“…The actions of many therapeutic drugs are known to be affected by the circadian rest-activity cycle. For some drugs used to treat hypertension and cancer, time of day that the drug is taken has a critical effect on efficacy and safety of the drug [23,24,46,47,60,68]. Thus, it is not surprising that the rest-activity cycle also modifies the effects of drugs of abuse.…”
Section: Circadian Activity Rhythms Also Modify the Effects Of Drugsmentioning
confidence: 99%